Sustained Repigmentation in Vitiligo and Leukodermas Using Melanocyte–Keratinocyte Transplantation: 7 Years of Data - Nuntawisuttiwong N; Yothachai P; Paringkarn T; Chaiyabutr C; Wongpraparut C; Silpa-archa N (Dove Medical Press, 2024)
Nuttaporn Nuntawisuttiwong,* Punyanut Yothachai,* Teerapat Paringkarn, Chayada Chaiyabutr, Chanisada Wongpraparut, Narumol Silpa-archa Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand*These authors contributed equally to this workCorrespondence: Narumol Silpa-archa, Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand, Tel +66 2419 4333, Email doctornarumol@gmail.comBackground: The autologous non-cultured melanocyte-keratinocyte transplantation procedure (MKTP) has emerged as an effective treatment for various types of vitiligo and leukodermas. However, there is limited data on the long-term outcomes of the MKTP, especially in Thai patients.Objective: To assess the long-term efficacy and safety of the MKTP in patients with vitiligo and other leukodermas.Methods: This retrospective observational study analyzed data from 23 patients who underwent the MKTP for vitiligo and other leukodermas at the Siriraj MKTP Clinic, Thailand, and had a follow-up period exceeding 12 months. Clinical characteristics and MKTP specifics were evaluated. Repigmentation outcomes were assessed using the Vitiligo Area Scoring Index (VASI).Results: Of the 23 patients (24 treated lesions), 78.3% had segmental vitiligo, while the others had nevus depigmentosus, nonsegmental vitiligo, or piebaldism. Most lesions (70.8%) were located on the face. At the 12-month follow-up, repigmentation showed an 80.8% ± 19.3% VASI improvement, which was sustained over 84 months with an 80%- 90% VASI improvement. There was no statistically significant difference in repigmentation outcomes between facial and non-facial lesions.Conclusion: The MKTP demonstrated long-term efficacy and safety in treating vitiligo and other leukodermas, with sustained repigmentation over 84 months. These findings support the use of the MKTP as an effective treatment option for patients with refractory vitiligo and leukodermas, particularly within Thai populations.Keywords: autologous non-cultured epidermal suspension, melanocyte-keratinocyte transplantation procedure, nevus depigmentosus, piebaldism, repigmentation, vitiligo